REPURCHASE INTENTION: PERAN BRAND IMAGE, BRAND TRUST, PERCEIVED VALUE, DAN SATISFACTION - Purwoko Purwoko; Muhammad Ali Fikri (Fakultas Ekonomi dan Bisnis Universitas Pekalongan, 2024)
The cosmetic industry in Indonesia continues to develop with the presence of various brands of products and types. Given the wide selection of cosmetic products, consumers often consider a variety of purchasing factors, such as brand image, brand trust, perceived value, and satisfaction. Repurchase intent relates to consumer behavior due to satisfaction and pleasure with previous experiences. This study aims to identify brand image, brand trust, perceived value, and satisfaction on repurchase intention. The research sample was taken from 85 respondents of halal cosmetic products in the Special Region of Yogyakarta. Data analysis of this study using Partial Least Square software. The findings in this study prove that brand image has no effect on repurchase intention, brand trust has an effect on repurchase intention, perceived value has an effect on repurchase intention, and satisfaction has no effect on repurchase intention.